Ethanol Fermentation from Rubber Cassava Starch (Manihot glaziovii) using Immobilized α-Amylase and Fermipan Yeast - Steven Purnomo; Tri Yahya Budiarso; Catarina Aprilia Ariestanti (agriTECH, 2026)
Rubber cassava (Manihot glaziovii) is one of the least attractive type of tubers for human consumption due to the high content of hydrogen cyanide (HCN) compounds, despite being rich in starch, proteins, and lipids. The variety can be used as an alternative raw material for ethanol production. Therefore, this research aimed to investigate the effects of immobilized enzymes and cells created using the entrapment method during starch hydrolysis and 84 hours of sugar fermentation, respectively. Starch, sugar, and ethanol contents were measured using the iodine, DNS, and Nicloux methods. The results showed that free enzymes in Treatment 1 (T1) hydrolyzed 100% of starch with a content of 6.50% in 30 minutes. At pH 7.07, immobilized cells in Treatment 2 (T2) produced 5.23% ethanol by converting 4.62% sugar over 84 hours. Immobilized enzymes were less productive in converting starch into sugar. Meanwhile, immobilized cells were more effective in using sugar from starch degradation to produce ethanol. These results reported the potential of rubber cassava as a viable source for ethanol production, emphasizing the efficiency of immobilized cells in the fermentation process.